2020
DOI: 10.1024/1012-5302/a000745
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Schutzmaßnahmen in der stationären Altenpflege

Abstract: Zusammenfassung. Hintergrund: Schutzmaßnahmen zur Eindämmung der COVID-19-Pandemie waren mit Isolationsmaßnahmen in der stationären Altenpflege verbunden. Aufgrund der bekannten negativen Auswirkungen von sozialer Isolation auf die Gesundheit wurden jedoch Diskussionen um die ethische Legitimation und Verhältnismäßigkeit dieser Maßnahmen geführt. Ziel: Der Beitrag soll darstellen, in welcher Form in pflegewissenschaftlichen Publikationen der Diskurs zu COVID-19-Schutzmaßnahmen stattgefunden hat und welche inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Aus einer Präferenz für informelle Pflege kann sich ein Spannungsfeld zwischen den Wünschen sowie Erwartungen (potenziell zukünftig) Pflegebedürftiger und den Möglichkeiten der Angehörigen ergeben [ 7 ]. Ein Mehrpersonenhaushalt weist auf ein höheres informelles Pflegepotenzial hin.…”
Section: Diskussionunclassified
“…Aus einer Präferenz für informelle Pflege kann sich ein Spannungsfeld zwischen den Wünschen sowie Erwartungen (potenziell zukünftig) Pflegebedürftiger und den Möglichkeiten der Angehörigen ergeben [ 7 ]. Ein Mehrpersonenhaushalt weist auf ein höheres informelles Pflegepotenzial hin.…”
Section: Diskussionunclassified
“…To ensure the safety of care home residents from infection with SARS-CoV-2, a contact ban was put into place in Germany in early March (Fischer et al ., 2020). As in many other European countries, this involved no visits from family members or friends, no contact with other residents, little to no movement within the care home building by residents, and staff wearing full protective clothing.…”
Section: Care Homes In Germany During the Spring Of 20201mentioning
confidence: 99%
“…Long before COVID-19, empirical evidence clearly showed that social isolation of older people, particularly with existing physical and mental deterioration, is strongly associated with anxiety, depression, general health deterioration and ultimately decreased life expectancy (Spitzer, 2018). Thus, current measures of protecting older people by reducing the amount of contact they have with significant others as well as reducing their mobility ( see the Care homes in Germany section) has the capacity to increase their risk of loneliness (Seifert and Hassler, 2020), poor health and mortality rather than reduce that risk (Fischer et al ., 2020). As Schulz-Nieswandt (2020) has argued, the pandemic threatens to erase the milestones achieved in the past two decades on providing care in residential settings that goes beyond physiological health and hygiene, and sets its focus on residents’ rights to personal freedom and participation.…”
Section: Introductionmentioning
confidence: 99%